Proses Negosiasi Antara Umkm A.M Tahu Dan Pemasok Bahan Baku Produksi - rizky, Ifan; Destiarni, Resti Prastika; Arfiyanti, Nurul; Musyafak; Rizky Kurniyanto, Ifan (Forum Agribisnis, 2024)
SME’s is an industry that plays an essential role in Indonesia’s economic development. As one of the SME’s, A.M Tahu has a problem fulfilling raw materials. The existence of special orders and moral hazard from suppliers were often obstacles in the production process, so A.M. Tahu needed to make a negotiation process to get affordable prices, good quality, and flexibility in the quantity of raw materials with a limited choice of suppliers. The negotiation process certainly does not immediately reach the desired agreement, but it needs to convince both parties. The research aimed to determine the negotiation process between A.M Tahu and raw material suppliers in reaching agreements. This study’s data are primary and secondary using AHP (Analysis Hierarchy Process) analysis and descriptive methods. The result showed that the negotiation process for A.M Tahu has several stages in reaching an agreement between the two parties, starting from preparation, meetings, offering, and signing a contract. A.M Tahu gets a more reasonable raw material price of IDR3,000 per kilogram than the price should be, soybean quantity flexibility, and reasonable quality assurance of soybean grain raw materials. A.M Tahu is also prioritized in choosing suppliers outside the sub-district and making raw material variables the primary consideration in supplier selection.